Structural basis for broad-spectrum binding of AT-9010 to flaviviral methyltransferases - Krejcova, Katerina; Boura, Evzen (Archives of virology, 2025)
AT-9010 (2'-methyl-2'-fluoro guanosine triphosphate) is a GTP analog whose prodrug, AT-752 is under consideration in human medicine as a potential antiviral drug against certain flaviviruses. It was previously believed to inhibit viral replication by acting primarily as a chain terminator. However, it was discovered recently that it also binds the GTP binding site of the methyltransferase (MTase) domain of the orthoflavivirus polymerase, thus interfering with RNA capping. Here, we investigated the binding of AT-9010 to Ntaya and Zika virus MTases. Structural analysis using X-ray crystallography revealed similar interactions between the base and sugar moieties of AT-9010 and key residues in both MTases, although differences in hydrogen bonding were observed. Our analysis also suggested that the triphosphate part of AT-9010 is flexible. Despite minor variations, the overall binding mode of AT-9010 was found to be the same for all of the flaviviral MTases examined, suggesting a structural basis for the efficacy of AT-9010 against multiple orthoflavivirus MTases.
Keywords: Models, Molecular; guanosintrifosfát; Humans; Methyltransferases; Guanosine Triphosphate; Viral Proteins; Protein Binding; virus zika; krystalografie rentgenová; vazebná místa; lidé; Crystallography, X-Ray; molekulární modely; Binding Sites; virové proteiny; antivirové látky; vazba proteinů; Antiviral Agents; Flaviviridae; methyltransferasy; Zika Virus